Encyclopedia of the Social and Solidarity Economy A Collective Work of the United Nations Inter-Agency Task Force on SSE (UNTFSSE) - Yi, Ilcheong (Edward Elgar Publishing, 2023)
The Encyclopedia of the Social and Solidarity Economy is a comprehensive reference text that explores how the social and solidarity economy (SSE) plays a significant role in creating and developing economic activities in alternative ways. In contrast to processes involving commodification, commercialisation, bureaucratisation and corporatisation, the SSE reasserts the place of ethics, social well-being and democratic decision-making in economic activities and governance. Identifying and analysing a myriad of issues and topics associated with the SSE, the Encyclopedia broadens the knowledge base of diverse actors of the SSE, including practitioners, activists and policymakers.